Speaking words of wisdom : the Beatles and religion - McGowan, Michael (Pennsylvania State University Press, 2024)
"A collection of essays by scholars of religion, music, philosophy, and culture exploring the Beatles' relationship to religion"-- Provided by publisher.
Keywords: Beatles -- Religion.; Beatles.; Rock music -- Religious aspects.; MUSIC / Individual Composer & Musician.